Comparison of the Dynamic and Static Corner Frequencies in Ground Motion Simulation: Cases Study of Jiuzhaigou Earthquake and Northridge Earthquake - Dang, Pengfei; Liu, Qifang; Ji, Linjian (Frontiers in Earth Science, 2022)
By using the stochastic finite-fault method based on static corner frequency (Model 1) and dynamic corner frequency (Model 2), we calculate the far-field received energy (FRE) and acceleration response spectra (SA) and then compare it with the observed SA. The results show that FRE obtained by the two models depends on the subfault size regardless of high-frequency scaling factor (HSF). Considering the HSF, the results obtained by Model 1 and Model 2 are found to be consistent. Then, similar conclusion was obtained from the Northridge earthquake. Finally, we analyzed the reasons and proposed the areas that need to be improved.